THE ACTION AT SANDFONTEIN (26 SEPTEMBER, 1914) - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
On the 21st August, 1914 the first plans for the German South West Africa campaign were discussed at Defence Headquarters, Pretoria, under chairmanship of Genl J. C. Smuts (Minister of Defence).